2003
DOI: 10.2527/2003.8171736x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of retail product weight and percentage using ultrasound and carcass measurements in beef cattle

Abstract: Data from 534 steers representing six sire breed groups were used to develop live animal ultrasound prediction equations for weight and percentage of retail product. Steers were ultrasonically measured for 12th-rib fat thickness (UFAT), rump fat thickness (URPFAT), longissimus muscle area (ULMA), and body wall thickness (UBDWALL) within 5 d before slaughter. Carcass measurements included in USDA yield grade (YG) and quality grade calculations were obtained. Carcasses were fabricated into boneless, totally trim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

14
52
9
22

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 66 publications
(97 citation statements)
references
References 23 publications
(49 reference statements)
14
52
9
22
Order By: Relevance
“…Similarly, Bjelka et al (2002) reported that the lowest content of separable fat in bulls was in conformation class E and it gradually increased through to the poorer classes. The significant negative correlation of carcass fat score with carcass meat proportion is similar to previous findings (May et al, 2000;Greiner et al, 2003). In accordance with Drennan et al (2008), significant positive correlations were obtained between carcass fat score with carcass fat proportion and perinephric and retroperitoneal fat.…”
Section: Assessorssupporting
confidence: 90%
See 2 more Smart Citations
“…Similarly, Bjelka et al (2002) reported that the lowest content of separable fat in bulls was in conformation class E and it gradually increased through to the poorer classes. The significant negative correlation of carcass fat score with carcass meat proportion is similar to previous findings (May et al, 2000;Greiner et al, 2003). In accordance with Drennan et al (2008), significant positive correlations were obtained between carcass fat score with carcass fat proportion and perinephric and retroperitoneal fat.…”
Section: Assessorssupporting
confidence: 90%
“…The positive correlation (r 5 0.52) between pre-slaughter scanned muscle depth and carcass meat proportion is within the range (0.30 to 0.84) found in some studies (Doorley, 2001;Tait et al, 2005), but higher than other (r 5 0.07 to 0.17) results (Hamlin et al, 1995;May et al, 2000;Greiner et al, 2003). The generally non-significant relationship between scanned muscle depth and the three indicators of carcass fat was as expected, and the high negative relationship with carcass bone proportion (r 5 20.75) was in agreement with Bailey et al (1986).…”
Section: Assessorssupporting
confidence: 70%
See 1 more Smart Citation
“…However, higher correlation coefficients between carcass and ultrasound measurement of the 12th rib (SBT and SF 12 ) were shown by Bullock et al (1991; Tables 3 and 4), in accordance with the results from Greiner et al (2003) study. Some studies reported an average absolute low difference between ultrasound and carcass measurement in the 12th rib fat (SBT and SF 12 ) for steers, such as 0.16 cm (Greiner et al, 2003) and 0.19 cm (Brethour, 1992). However, our results showed averaged differences of 0.5 cm for cull dairy cows, likely because the magnitude of the differences between SF 12 and SBT increases as SF 12 increases (Brethour, 1992;Greiner et al, 2003).…”
Section: Animal Live Recording Characteristicssupporting
confidence: 88%
“…Some studies reported an average absolute low difference between ultrasound and carcass measurement in the 12th rib fat (SBT and SF 12 ) for steers, such as 0.16 cm (Greiner et al, 2003) and 0.19 cm (Brethour, 1992). However, our results showed averaged differences of 0.5 cm for cull dairy cows, likely because the magnitude of the differences between SF 12 and SBT increases as SF 12 increases (Brethour, 1992;Greiner et al, 2003). SF 12 and SBT determined the subcutaneous fat thickness on the 12th rib by different methods.…”
Section: Animal Live Recording Characteristicsmentioning
confidence: 99%